1999
DOI: 10.1080/01616412.1999.11740931
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence factors for chronic subdural hematomas after burr-hole craniostomy and closed system drainage

Abstract: Recurrence of chronic subdural hematoma after burr-hole craniostomy and closed system drainage is not uncommon. We sought to identify risk factors for recurrence. In 121 patients, various factors including age, initial neurologic status, hematoma thickness, computed tomographic density of the hematoma, midline shift, multiplicity, systemic disease, and drainage volume were compared retrospectively between nonrecurring cases and recurring cases. Recurrence was noted in 10 cases (8.3%). In recurring cases, the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
1
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(47 citation statements)
references
References 15 publications
2
42
1
2
Order By: Relevance
“…In the literature, re-intervention rates after burr-hole surgery with subdural drains vary between 8.3 and 26.5 % (5,6,14,19,20,24,35). Results from the present series, and 7.6 % obtained by the akin strategy reported by Gazzeri et al (7), thus represent comparatively low incidences of recurrence.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…In the literature, re-intervention rates after burr-hole surgery with subdural drains vary between 8.3 and 26.5 % (5,6,14,19,20,24,35). Results from the present series, and 7.6 % obtained by the akin strategy reported by Gazzeri et al (7), thus represent comparatively low incidences of recurrence.…”
Section: Discussionmentioning
confidence: 44%
“…At present, burr-hole surgery with subdural closed-drainage system is the most commonly chosen strategy. This technique was repeatedly shown to be effective and safe (7,8,14,18,20,22,23,32,34,36,37). More recently, enlarged single-burr-hole trepanation in combination with a suction-assisted subgaleal draining system has also earned consideration as a safe and effective approach (7).…”
Section: Introductionmentioning
confidence: 99%
“…Recurrence rates after burr hole surgery vary between 8.3% and 26.5%. [4][5][6][7][8][9][10] Numerous factors have been associated with recurrence of CSDH. Despite the common nature of CSDH, we were unable to locate a previous study that compared recurrence rates and outcome of single versus double burr holes in the treatment of CSDH.…”
Section: Introductionmentioning
confidence: 99%
“…3,19,38,40) Multilobular hematoma was also reported as a causative factor of recurrent CSDH. 23) We found that the presence of thin subdural hematoma or effusion in the side contralateral to the first operation carried a high risk of recurrence.…”
Section: Surgical Treatment Of Csdhmentioning
confidence: 99%